Shortage of skilled workers: a paradox of the Indian economy - Hajela, R (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2012)
As a country endowed with labour, India's situation is at best ironic. On the one hand, domestic economic growth has created huge employment demand and job opportunities, while on the other, a shortage of skills is making more people unemployable. What adds to the irony is that there are 17 central government ministries that offer skill development initiatives through school education, institutes of higher learning and specialised vocational training institutes. The large size of the population and training structure, has better labour productivity (indicating higher skills). This paper argues that India lacks sufficient skilled workers as its existing vocational training system does not target the casual or informal workforce, which constitutes over 90 per cent of India's working population. This paper examines the vocational training offered for specific skills in construction and highlights the lack of inclusiveness and poor coordination in the complex federal government structure.